Pancreatic Adenocarcinoma Producing Parathyroid Hormone-Related Protein. (15th August 2017) - Yamada, Reiko; Tanaka, Kyosuke; Inoue, Hiroyuki; Sakuno, Takashi; Harada, Tetsuro; Yoshizawa, Naohiko; Miura, Hiroshi; Takeuchi, Toshihumi; Nakamura, Misaki; Katsurahara, Masaki; Hamada, Yasuhiko; Horiki, Noriyuki; et al.
Abstract : A 48-year-old woman presented to our hospital with a 1-year history of a continuous high fever. She was diagnosed with metastatic pancreatic adenocarcinoma accompanied by leukocytosis without infection. Her serum concentration of granulocyte colony-stimulating factor was highly elevated. Forty-five days after initiating chemotherapy, she was readmitted because of a neuropsychiatric disturbance and hypercalcemia. Her serum concentration of parathyroid hormone-related protein (PTH-rP) was elevated. A pretreatment biopsy specimen showed strong cytoplasmic immunoreactivity to anti-PTH-rP antibody, suggesting that overproduction of PTH-rP accounted for the hypercalcemia. Although the patient regained consciousness after treatment, she died of progressive disease 60 days after chemotherapy.